PERAN LINGKUNGAN BELAJAR RAMAH ANAK TERHADAP PERKEMBANGAN HOLISTIK ANAK USIA DINI - Aryani, Widia; Wardany, Heru; Royani, Ida (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
This study aims to describe and analyze the implementation of a child-friendly learning environment in supporting the holistic development of early childhood at a PAUD institution. The research employs a descriptive qualitative approach with data collection techniques consisting of in-depth interviews, observations, and documentation. The subjects of the study include teachers, parents, and children involved in the learning activities at the PAUD institution. The findings show that a safe, comfortable, and stimulating physical environment, along with the teacher's role in supporting children's social-emotional and cognitive development, positively impacts early childhood development. Additionally, parental involvement in the learning process and the wise use of technology also plays a significant role in creating an environment that supports the holistic development of children. The study concludes that the implementation of a child-friendly learning environment can improve the quality of learning and support children's overall development. This research contributes to the development of educational policies and practices in Indonesia by emphasizing the importance of child-friendly learning environments.